EEG Oscillation Evidences of Enhanced Susceptibility to Emotional Stimuli during Adolescence - Meng, Xianxin; Liu, Wenwen; Zhang, Ling; Li, Xiang; Yao, Bo; Ding, Xinsheng; Yuan, JiaJin; Yang, Jiemin (Frontiers in Psychology, 2016)
Background: Our recent event-related potential (ERP) study showed that adolescents are more emotionally sensitive to negative events compared to adults, regardless of the valence strength of the events. The current work aimed to confirm this age-related difference in response to emotional stimuli of diverse intensities by examining EEG oscillatory power in time-frequency analysis. Methods: Time-frequency analyses were performed on the Electroencephalography (EEG) data recorded for highly negative (HN), moderately negative (MN) and Neutral pictures in 20 adolescents and 20 adults during a covert emotional task. The results showed a significant age by emotion interaction effect in the theta and beta oscillatory power during the 500-600ms. Results: Adolescents showed significantly less pronounced theta spectral power (5.5-7.5Hz) for HN stimuli, and larger beta (18-20Hz) spectral power for both HN and MN stimuli, in comparison with neutral stimuli. By contrast, adults exhibited no significant emotion effects in theta and beta frequency bands. In addition, the analysis of the alpha spectral power (10.5-12 Hz; 850-950ms) showed a main effect of emotion, while the emotion by age interaction was not significant. Irrespective of adolescents or adults, HN and MN stimuli elicited enhanced alpha suppression compared to Neutral stimuli, while the alpha power was similar across HN and MN conditions. Conclusions: These results confirmed prior findings that adolescents are more sensitive to emotionally negative stimuli compared to adults, regardless of emotion intensity, possibly due to the developing prefrontal control system during adolescence.